2010
DOI: 10.1016/j.imlet.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TLR4 signaling prolongs Treg-dependent murine islet allograft survival

Abstract: Toll-like receptors (TLRs) provide an important link between innate and adaptive immune system. We hypothesized that the recognition of endogenous TLR4 ligands is occurring at the time of transplantation, and these innate signals drive the inflammation and affect alloimmune responses. We confirmed that early after transplantation of allogenic islets, transcripts for TLR4 as well as potential ligands were released or upregulated. In an allogenic islet transplantation model, genetic disruption of TLR4 on donor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
(48 reference statements)
0
30
0
Order By: Relevance
“…It has been reported that TLR4 signaling is involved in allograft survival through a Treg-dependent mechanism1819. We next determined the number of Tregs in the DLNs of mice treated with various lentiviral vectors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TLR4 signaling is involved in allograft survival through a Treg-dependent mechanism1819. We next determined the number of Tregs in the DLNs of mice treated with various lentiviral vectors.…”
Section: Resultsmentioning
confidence: 99%
“…Using small interfering RNA (siRNA) to silence the expression of the TLR signal adaptors MyD88 and TRIF prolongs allograft survival in a BALB/C to C57BL6 cardiac transplantation model18. In an islet transplantation model19, genetic disruption of TLR4 on donor islets had no effect on allograft survival, whereas TLR4 deficiency in recipients led to prolonged graft survival, which was dependent upon the presence of CD4 + CD25 + Foxp3 + Tregs. These two studies raised that silencing TLR signaling in organ transplantation generated Tregs, which facilitated graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, administration of an anti-CD25 antibody to these mice depleted Tregs and broke tolerance. There is accumulating evidence that TLR2 and TLR4 activation inhibits Treg activation [62, [70][71][72]. It is known that neither Tregs nor Th17 represent a terminally differentiated phenotype, given the plasticity of T-cell differentiation [73].…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…The addition of rapamycin further extended allograft survival and was associated with an increase in the numbers of CD4 þ CD25 þ FoxP3 þ regulatory T cells and Th2 deviation [27 & ]. TLR4 appears to play a significant role in experimental islet transplantation, as TLR4 deficiency in recipients [28] but not in donors [28,29] delayed rejection of graft across a major antigen mismatch [28]. In Goldstein et al's [24] original experiments, while MyD88 deficiency prevented rejection of skin allografts across a minor MHC mismatch, neither TLR2 nor TLR4 was found to be protective.…”
Section: Toll-like Receptors In Acute Allograft Rejectionmentioning
confidence: 99%